Creatine supplementation and swim performance: A brief review - Hopwood, M. J.; Graham, K.; Rooney, K. B. (Journal of Sports Science & Medicine, 2006)
Nutritional supplements are popular among athletes participating in a wide variety of sports. Creatine is one of the most commonly used dietary supplements, as it has been shown to be beneficial in improving performance during repeated bouts of high-intensity anaerobic activity. This review examines the specific effects of creatine supplementation on swimming performance, and considers the effects of creatine supplementation on various measures of power development in this population. Research performed on the effect of creatine supplementation on swimming performance indicates that whilst creatine supplementation is ineffective in improving performance during a single sprint swim, dietary creatine supplementation may benefit repeated interval swim set performance. Considering the relationship between sprint swimming performance and measurements of power, the effect of creatine supplementation on power development in swimmers has also been examined. When measured on a swim bench ergometer, power development does show some improvement following a creatine supplementation regime. How this improvement in power output transfers to performance in the pool is uncertain. Although some evidence exists to suggest a gender effect on the performance improvements seen in swimmers following creatine supplementation, the majority of research indicates that male and female swimmers respond equally to supplementation. A major limitation to previous research is the lack of consideration given to the possible stroke dependant effect of creatine supplementation on swimming performance. The majority of the research conducted to date has involved examination of the freestyle swimming stroke only. The potential for performance improvements in the breaststroke and butterfly swimming strokes is discussed, with regards to the biomechanical differences and differences in efficiency between these strokes and freestyle.